2020
DOI: 10.5114/ada.2019.83975
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin/cortisol ratio – a marker of psoriasis severity

Abstract: Introduction: The hypothalamic-pituitary-adrenal (HPA) axis plays a crucial role in systemic homeostasis and hormonal regulation of metabolic and immune functions. A similar HPA axis analog exists in the skin, where it regulates inflammation, cell proliferation and differentiation. Data regarding central HPA axis dysregulation in psoriasis are interesting but so far inconclusive. Aim: In the study we attempted to determine whether central HPA axis serum components correlate with psoriasis severity. Material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These studies suggest that some psoriatic patients may have reduced cortisol response. Such inability to produce an adequate upregulation of cortisol in response to stress is thought to carry important pathogenetic implications given the immunosuppressive action of cortisol [8]. Indeed, glucocorticoids inhibit the differentiation of T helper cells into Th1 and increase the production of Th2 cytokines [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that some psoriatic patients may have reduced cortisol response. Such inability to produce an adequate upregulation of cortisol in response to stress is thought to carry important pathogenetic implications given the immunosuppressive action of cortisol [8]. Indeed, glucocorticoids inhibit the differentiation of T helper cells into Th1 and increase the production of Th2 cytokines [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological stress has been for long recognized as a trigger factor in psoriasis, and a systematic review of the literature found that a probable temporal association between psychological stress and onset, recurrence, and severity of psoriasis [2]. The exact mechanisms behind this association have not been fully elucidated, though alterations in hypothalamic-pituitary-adrenal (HPA) axis resulting in an altered response to stress could be demonstrated in psoriasis by serum and salivary cortisol measurements [3][4][5][6][7][8], thus being thought to have pathogenetic implications [9]. Despite the large number of studies on stress in psoriasis, limited data are currently available on salivary cortisol in psoriatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of the hypothalamic-pituitary-adrenal axis may be responsible for the release of pro-inflammatory cytokines involved in the pathogenesis of psoriasis. They found a positive correlation between morning ACTH/cortisol ratio and disease severity evaluated using the PASI score [72]. There is evidence of a correlation between salivary cortisol concentration and psoriasis severity.…”
Section: Hormone-related Markersmentioning
confidence: 96%